The Effect of Intellectual Capital, Islamic Corporate Social Responsibility, and Islamic Corporate Governance on Firm Value in Islamic Banks - Ahmad; Muntu Abdullah; Fitriaman (Takaza Innovatix Labs Ltd., 2025)
This study offers several contributions to the literature on Islamic banking and firm value. First, unlike most previous studies that measure firm value using market-based indicators such as Price to Book Value (PBV) and Tobin’s Q, this research employs Economic Value Added (EVA) as a proxy for firm value. EVA provides a more comprehensive assessment because it reflects the company’s ability to create real economic value after considering the cost of capital. Second, this study integrates Intellectual Capital, Islamic Corporate Social Responsibility (ICSR), and Islamic Corporate Governance (ICG) into a single analytical framework, allowing a more comprehensive examination of the combined influence of these Sharia-based non-financial factors on firm value. Third, this research focuses on Islamic Commercial Banks in Indonesia during the 2021–2024 period, a period characterized by significant developments in the Islamic banking industry following digital transformation and industry consolidation. Therefore, this study is expected to enrich the empirical evidence regarding the determinants of firm value in Islamic banking and provide insights for academics, practitioners, and regulators in strengthening the sustainability and competitiveness of Islamic financial institutions.